2011
DOI: 10.1021/nn200610r
|View full text |Cite
|
Sign up to set email alerts
|

Gyroid Nanoporous Membranes with Tunable Permeability

Abstract: Understanding the relevant permeability properties of ultrafiltration membranes is facilitated by using materials and procedures that allow a high degree of control on morphology and chemical composition. Here we present the first study on diffusion permeability through gyroid nanoporous cross-linked 1,2-polybutadiene (1,2-PB) membranes with uniform pores that, if needed, can be rendered hydrophilic. The gyroid porosity has the advantage of isotropic percolation with no need for structure prealignment. Closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 54 publications
1
96
0
Order By: Relevance
“…The diffusion permeability of different solutes (antibiotics, proteins, and several biomolecules) across gyroid nanoporous 1,2-polybutadiene (1,2-PB) membranes was studied by Li et al [153] using Eq. (18).…”
Section: Filtration and Membranesmentioning
confidence: 99%
“…The diffusion permeability of different solutes (antibiotics, proteins, and several biomolecules) across gyroid nanoporous 1,2-polybutadiene (1,2-PB) membranes was studied by Li et al [153] using Eq. (18).…”
Section: Filtration and Membranesmentioning
confidence: 99%
“…The improvement provided by the S skin samples is particularly interesting. In a comparative study of glucose permeability through 1,2-PB nanoporous membranes [31], we have observed that the presence of skin layer diminishes the effective diffusion coefficient by a factor of 5.7 compared to the porous surface. This effect is correlated to decreased surface porosity due to the compact nature of the skin layer, irregularly interrupted by porous defects [31].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that BCP-derived membranes with bicontinuous nanopore morphologies have also been examined as ultrafiltration membranes. [88,89] These membranes did not require domain alignment for fabrication and exhibited fairly sharp MWCOs, but showed fouling and lower flux owing to their large tortuosity. [89] …”
Section: Flow-through Nanoporous Membranes For Chemical Separationsmentioning
confidence: 99%